2007
DOI: 10.1007/s10209-007-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to telecare among older people, professional care workers and informal carers: a preventative strategy or crisis management?

Abstract: This paper reports findings from an attitudinal survey towards telecare that emerged from twenty-two focus groups comprising ninety-two older people, fifty-five professional stakeholders and thirty-nine carers. These were convened in three different regions of England as a precursor to telecare service development. The results from this study suggest that informants' views were shaped by prior knowledge of conventional health and social care delivery in their locality and the implication is that expectations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 14 publications
1
31
0
3
Order By: Relevance
“…If the system is given a chance to fit into the everyday lifestyle of the elderly, giving them a sense of security and at the same time allowing them to lead a more independent life, its acceptance will increase significantly. 25,69,89 A study performed by Bujnowska and Pirogowicz 64 showed that approximately 41% of the elderly had a favorable attitude toward e-health services and were willing to use it if/when offered an opportunity to do so. A substantial majority (84%) of supporters expressed a desire to receive simple medical recommendations via mobile phone or a computer, although significant majorities (61% and 60%, respectively) wanted to receive the results of tests by email or SMS reminders for scheduled visits or prescribed medications.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…If the system is given a chance to fit into the everyday lifestyle of the elderly, giving them a sense of security and at the same time allowing them to lead a more independent life, its acceptance will increase significantly. 25,69,89 A study performed by Bujnowska and Pirogowicz 64 showed that approximately 41% of the elderly had a favorable attitude toward e-health services and were willing to use it if/when offered an opportunity to do so. A substantial majority (84%) of supporters expressed a desire to receive simple medical recommendations via mobile phone or a computer, although significant majorities (61% and 60%, respectively) wanted to receive the results of tests by email or SMS reminders for scheduled visits or prescribed medications.…”
mentioning
confidence: 99%
“…25,69,93 Until now, telecare solutions have tended to be closed, single-purpose, inflexible, and specialized. The needs of seniors vary widely and can change over time.…”
mentioning
confidence: 99%
See 3 more Smart Citations